2021
DOI: 10.1001/jamapediatrics.2020.3595
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Children vs Adults Carrying Severe Acute Respiratory Syndrome Coronavirus 2 Asymptomatically

Abstract: Children have been suggested as the facilitators of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission and amplification, 1 because many affected children might be asymptomatic. 2,3 Accordingly, social and public health policies, such as school closure, have been implemented in many countries. However, the role of children in asymptomatically carrying SARS-CoV-2 needs to be further explored. In this study, we investigated the frequency of individuals carrying SARS-CoV-2 among children ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 6 publications
(12 reference statements)
3
44
0
3
Order By: Relevance
“…9 However, more recent studies report that children are less likely to get infected after contact with a SARS-CoV-2-positive individual. [10][11][12][13][14] It has been suggested that children and adolescents have similar viral loads 15 16 and may therefore be as likely to transmit SARS-CoV-2 as adults. 17 18 In addition, the viral load may be similar in asymptomatic and symptomatic individuals.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, more recent studies report that children are less likely to get infected after contact with a SARS-CoV-2-positive individual. [10][11][12][13][14] It has been suggested that children and adolescents have similar viral loads 15 16 and may therefore be as likely to transmit SARS-CoV-2 as adults. 17 18 In addition, the viral load may be similar in asymptomatic and symptomatic individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Some estimates suggest that 80% of adults with the virus are aymptomatic. 82 Similarly, we do not know the testing protocol for US politicians and other attendees of the Rose Garden event. While it seems that transmission from children is rare, the difficulty in maintenance of social distancing between children in schools can permit SSEs to arise; it seems the same applies to adults in the Rose Garden.…”
mentioning
confidence: 99%
“…The few available data from other parts of Italy have suggested a non-negligible risk of transmission of SARS-CoV-2 in the schools [4], while other studies conducted in other European Countries such as Germany [5] and Ireland [6] have reported a very low risk of secondary infection from children attending schools. In a previous study conducted during the school closure for the first SARS-CoV-2 outbreak in Italy, we observed a lower frequency of asymptomatic carriers among children as compared to adults (1.2% vs 9.2%, respectively) in hospital settings [7]. However, no comparable data are available after the school reopening.…”
Section: Introductionmentioning
confidence: 67%
“…In particular, two clinical pathways were established in the Ca' Granda Ospedale Maggiore Policlinico for non-suspected and suspected cases of SARS-CoV-2 infection, to avoid any potential contact (and infection spread) between these two groups of patients [8]. A nasopharyngeal swab specimen was collected for the detection of SARS-CoV-2 in all patients admitted in the short stay observation of the ED, irrespective of their clinical presentation [7]. The swab was sampled by a trained nurse according to a standardized procedure [9].…”
Section: Methodsmentioning
confidence: 99%